CINTA RUPIAH: EDUKASI UANG DAN PENGELOLAANNYA BAGI SISWA SEKOLAH DASAR - Liana Dewi; Revalina Yunijar; Via Fitriani (LPPM Universitas Mayasari Bakti, 2025)
The inability to manage finances well often stems from a lack of financial literacy. Millennials and Generation Z face low financial literacy, which has a significant impact on economic well-being. To anticipate and break the path of low literacy across generations, it is necessary to educate the Alpha generation from an early age regarding money and simple patterns of its management. The Alpha generation is expected to be the generation with a better level of financial literacy. A community service activity themed